The Impact of Multi-Layered Diffusionary Processes on Musical Evolution: The Global Nature, and Hawaiian, Spanish and African Roots of Delta Blues Culture - Strait, John Byron; Fujimoto-Strait, Ava Rei (European Scientific Journal, ESJ, 2017)
As a distinct musical form, blues music from the Mississippi Delta has been extensively studied by musicologists, ethnomusicologists, historians and folklorists. As has been the case with the larger public attracted to this intriguing musical genre, much of this academic attention has treated blues as just that - something one listens to. We argue that blues represents far more than just sound or entertainment, rather it represents a broad cultural milieu from which a distinctive musical culture evolved. Moreover, the musical evolution associated with blues did not occur in a vacuum, it was generated and facilitated by various forms of cultural exchange occurring over time and space. Further, the forms of cultural exchange responsible for the evolution of Delta blues culture were and continue to be truly global in scope. In this paper, by highlighting Hawaiian, Spanish and African influences, we discuss the geographical processes associated with the evolution of blues music and focus on the multi-layered forms of global diffusion responsible for what has been referred to as “Delta blues.” Through a discussion of this form of blues music, we focus attention on the complex inter-relationships evident between and among different people and different places, and highlight how global interactions generated a truly unique music form.